1992
DOI: 10.1007/bf00229012
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of the legs of a slow-walking cat

Abstract: Summary. On the basis of behavioural studies the influences that coordinate the movement of the legs of a slowly walking cat have been investigated. The recording method applied here allows for the measurement of forward and backward movement of the legs which are called swing and stance movements, respectively. Influences between contralateral legs, i.e. both front legs or both hind legs, are stronger than those occurring between ipsilateral legs, i.e. front and hind leg of the same side. Influences which coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…WALKNET is based on the behavioural rules that have been derived from the experimental studies on walking stick insects. Similar rules have been found for the walking crayfish (Cruse 1990) and cats (Cruse & Warnecke 1992). The core of WALKNET consists of a set of six single-leg controllers, each of which is built by a number of distinct modules that are responsible for solving particular subtasks.…”
Section: (D ) Behaviour Is Investigated First Followed By Simulationmentioning
confidence: 82%
“…WALKNET is based on the behavioural rules that have been derived from the experimental studies on walking stick insects. Similar rules have been found for the walking crayfish (Cruse 1990) and cats (Cruse & Warnecke 1992). The core of WALKNET consists of a set of six single-leg controllers, each of which is built by a number of distinct modules that are responsible for solving particular subtasks.…”
Section: (D ) Behaviour Is Investigated First Followed By Simulationmentioning
confidence: 82%
“…This effect has been documented in curvewalking stick insects (Jander, 1985). Similarly, the strong contralateral coupling according to rule 1 between hind legs in walking cats (Cruse and Warnecke, 1992) is probably mostly due to unilateral load-dependent feedback from Golgi tendon organs that prevent flexion and, therefore, lift-off (reviewed by Pearson, 1995). In stick insects, the centre of gravity lies behind the hind leg coxae, so the swing movements of a hind leg cause increased loading of the ipsilateral middle leg, though to a lesser extent than of the contralateral hind leg.…”
Section: Differences Between Leg Pairsmentioning
confidence: 98%
“…Termination of locomotion could be achieved by simply removing the excitatory input to this region [20][21][22]. Further support for the importance of interlimb coordination was obtained by Cruse and Warnecke (1992) [23], in the intact cat and by Giuliani and Smith (1987) [24], in the chronic spinal cat, Th latter authors found that the coupling between hind leg movements during stepping in the air was weaker fol lowing deafferentation of a hindlimb. They showed that during the majority of locomotor movements, the bilat eral stepping was characterized by irregular phasing, with the intact hindlimb stepping at a faster frequency than the deafferented leg.…”
Section: Evidence For Cpg In Catmentioning
confidence: 99%